UPAYA HUKUM DALAM PENYELESAIAN TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA DI LUAR PENGADILAN DI KOTA SAMARINDA - Agustina Friskawanti (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT The settlement of non-litigation or off-court domestic violence cases is also very important because it has a positive impact and effect for the relationship of both parties for the sake of the unity of the household and family reuniting and the legal status as the husband of the head of the household, the wife of the housewife and children from the fruit of their love. As regulated in Article 1 of Law No. 1 of 1974 on Marriage which is the main purpose of the marriage itself. The marriage that is built forms a small scope which is the first part of the community that is the family as regulated in Article 2 of Law Number 23 Year 2004 on the Elimination of Domestic Violence, that the family consists of husband, wife and children basically. In this case the family as a small community that became the first socialization before knowing the wider community, therefore the integrity of the family is very important to be maintained and upheld.